(untitled) (Research, Society and Development, 2021)
This article has as general objective to analyze the importance of literacy in the early years of education through a literature review, which used inclusion and exclusion criteria in research databases, thus serving as the main bias to analyze the documentation addressing the topic recently and its impact on the formation of the child as a literate and literate subject. Whose literacy is the teaching, development and competent use of reading and writing in the social environment, while literate, the definition is simplified for the subject who knows how to read and write through the use of a code. Thus, it was concluded through the analysis of the literature that the action of teaching with literacy in turn causes difficulties for the literacy teacher, especially in an attempt to reconcile pedagogical practice with theory.